Flame-retardant polycarbonate material as well as preparation method and application thereof

By improving the composition and processing technology of flame-retardant polycarbonate materials, the problems of environmental protection and flame retardant performance degradation after aging in the existing technology are solved, and high temperature resistance, environmental protection, flame retardant performance and stability of mechanical properties are achieved.

CN120648193APending Publication Date: 2025-09-16ZHUZHOU DIBO PHOTOELECTRIC MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510739926.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing flame-retardant polycarbonate materials have the risk of exceeding PFAS performance standards in terms of environmental protection, and their flame retardant performance declines after double 85 aging and cannot reach the V0 level.

Method used

Using polycarbonate raw materials, silicone flame retardants, anti-dripping agents, anti-hydrolysis agents, heat stabilizers, antioxidants and dispersants, through twin-screw processing and molding, we prepare high-temperature-resistant, environmentally friendly flame-retardant polycarbonate materials, avoiding the use of halogens and PFAS substances, ensuring that the material maintains flame retardant properties under high temperature and aging conditions.

Benefits of technology

The prepared material has excellent tensile strength and elongation at break under GB/T1040.3 and ASTM D882 standards, reaches V0 level in the UL94 flame retardant test, and has no cracking or deformation after 1500 hours of double 85 aging, with stable flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005434369410000081
    Figure BDA0005434369410000081
  • Figure BDA0005434369410000091
    Figure BDA0005434369410000091
Patent Text Reader

Abstract

The invention relates to the technical field of polymer modified materials, in particular to a flame-retardant polycarbonate material, a preparation method of the flame-retardant polycarbonate material and application of the flame-retardant polycarbonate material, and particularly provides the flame-retardant polycarbonate material which comprises the following components in parts by mass: 80-99 parts of a polycarbonate raw material, 0.05-2 parts of a dispersing agent, 0.1-1 part of an antioxidant and 0.1-1 part of a lubricant. The flame retardant composition comprises the following components in parts by weight: 0.1-10 parts of an organic silicon flame retardant, 0.1-0.8 part of an anti-dripping agent, 0.3-2 parts of an anti-hydrolysis agent, 0.1-1 part of a heat stabilizer, 0.05-1 part of an antioxidant and 1-4 parts of black masterbatch. According to the present invention, the casting process molding of the polycarbonate film material with the thickness of 0.5 mm can be met, and the UL94 flame retardant test of the film product subjected to the casting molding can achieve the V0 level under the GB / T1040.3 and ASTM D882 standard determination, and the film product has no deformation within 30 min at the temperature of 140 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer modified materials, in particular to a flame retardant polycarbonate material, a preparation method of the flame retardant polycarbonate material, and applications of the flame retardant polycarbonate material. Background Art

[0002] The application of polycarbonate film products in new energy vehicles, energy storage and 3C industries is increasing. In new energy vehicles and energy storage products, due to the high requirements for their use environment and service life, there are obvious new requirements for the double 85 aging performance of materials to ensure the reliability of polycarbonate film products under long-term multi-environmental conditions.

[0003] Patent No. CN119144139A discloses a high-impact, thin-walled flame-retardant polycarbonate material, its preparation method and application. Its specific components are: 84.5-95 parts of polycarbonate, 0.5-1.5 parts of sulfonate flame retardant, 2-5 parts of phosphorus flame retardant, 1-5 parts of amino polyacrylonitrile, 0.1-1 part of mesophase carbon microspheres, 1-5 parts of toughening agent and 0.1-0.5 parts of antioxidant.

[0004] Although the thin-walled flame-retardant polycarbonate material provided by this technical solution can reach the UL-94 flame retardant V0 level at 0.5mm, it has the risk of exceeding the PFAS performance standard at the environmental protection level and does not meet the domestic and international control requirements for PFAS series substances; at the same time, after 1500 hours of double 85 aging, the flame retardant performance of the product has a significant decline and cannot reach the flame retardant V0 level. Summary of the Invention

[0005] The present invention aims to solve the problems existing in the prior art and provides the following technical solutions:

[0006] A flame retardant polycarbonate material comprising the following components in the following mass fractions:

[0007] The polycarbonate raw material is 80-99 parts, the dispersant is 0.05-2 parts, the silicone flame retardant is 0.1-10 parts, the anti-dripping agent is 0.1-0.8 parts, the anti-hydrolysis agent is 0.3-2 parts, the heat stabilizer is 0.1-1 parts, the antioxidant is 0.05-1 parts, and the black masterbatch is 1-4 parts.

[0008] As an improvement of the above technical solution, the polycarbonate raw material is composed of one or both of polycarbonate granules and polycarbonate powder;

[0009] The average molecular weight of the polycarbonate is 50000Da-70000Da;

[0010] The melt mass flow rate is not higher than 6.5g / 10min under the test conditions of 300℃ and 1.2kg;

[0011] The particle size of the polycarbonate raw material is 10um-500um.

[0012] As an improvement of the above technical solution, the dispersant is composed of one or both of hydroxy silicone oil and dimethyl silicone oil;

[0013] The viscosity of the dispersant at 25° C. ranges from 500 to 1000 cST.

[0014] As an improvement of the above technical solution, the organosilicon flame retardant is composed of one or more of hydroxyphenylsiloxane, organosilisesquioxane, and methylphenylsilsesquioxane.

[0015] As an improvement of the above technical solution, the anti-dripping agent is composed of one or more of powdered polytetrafluoroethylene, polytetrafluoroethylene wax, and silicone-coated polytetrafluoroethylene;

[0016] The content of polytetrafluoroethylene in the silicone-coated polytetrafluoroethylene is ≥80%.

[0017] As an improvement of the above technical solution, the anti-hydrolysis agent is composed of one or more of carbodiimide type, isocyanate type, and polyester type.

[0018] As an improvement of the above technical solution, the heat stabilizer is composed of one or more of calcium-zinc composite stabilizer, organic tin type, and rare earth type.

[0019] As an improvement of the above technical solution, the toner content in the black masterbatch is 25%-40%.

[0020] As an improvement of the above technical solution, the antioxidant is composed of one or more of hindered phenol antioxidants and phosphite antioxidants.

[0021] A method for preparing a flame retardant polycarbonate material, comprising the following steps:

[0022] The components are taken according to the ratio and formed by a twin-screw one-step process or a twin-screw multi-step process.

[0023] As an improvement to the above technical solution, the temperature is controlled at 220-270°C during the processing.

[0024] As an improvement to the above technical solution, when a twin-screw is used for processing, the aspect ratio of the twin-screw is 36:1, 40:1; 44:1, 48:1.

[0025] Application of flame-retardant polycarbonate material, wherein the flame-retardant polycarbonate material is applied to film formed by casting or calendering extrusion.

[0026] As an improvement of the above technical solution, the film is applied to the 3C electronic products industry, the new energy battery industry, and the energy storage industry.

[0027] Beneficial effects of the present invention:

[0028] A polycarbonate base material, an organosilicon flame retardant, an anti-dripping agent, an anti-hydrolysis agent, a thermal stabilizer, an antioxidant, and a dispersant are processed in one or more steps to prepare a high-temperature-resistant, environmentally friendly, flame-retardant polycarbonate modified material. The material of the present invention can meet the requirements of a 0.5mm thick polycarbonate film material casting process. The cast film product has a tensile strength of ≥55MPa and an elongation at break of ≥80% under the GB / T1040.3 and ASTMD882 standards. Its UL94 flame retardancy test can reach the V0 level and can withstand no deformation within 30 minutes at 140°C. Its material composition does not contain halogens and PFAS series substances. At the same time, its double 85 has excellent thermal aging performance and can maintain no cracking or deformation within 1500 hours. Its flame retardancy can maintain a V0 flame retardancy level. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples. Those skilled in the art will readily understand the other advantages and benefits of the present invention from the disclosure herein. The present invention may also be implemented or applied through various other specific embodiments, and the details in this specification may be modified or altered based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] Although the thin-walled flame-retardant polycarbonate material provided by existing technology can reach the UL-94 flame retardant V0 level at 0.5mm, it has the risk of exceeding the PFAS performance standard in terms of environmental protection, and does not meet the domestic and international control requirements for PFAS series substances; at the same time, after 1500 hours of double 85 aging, the flame retardant performance of the product has a significant decline and cannot reach the flame retardant V0 level.

[0031] Example 1

[0032] In this embodiment, the mass fraction of each component in the flame retardant polycarbonate material is as follows:

[0033] 85.1 parts of polycarbonate granules, 10 parts of polycarbonate powder, 1.2 parts of silicone flame retardant, 0.4 parts of anti-dripping agent, 0.1 parts of antioxidant, 0.5 parts of anti-hydrolysis agent, 0.5 parts of heat stabilizer, 0.2 parts of dispersant, and 2 parts of black masterbatch.

[0034] The average molecular weight of the polycarbonate is 50,000.

[0035] Under the test conditions of 1.2kg, it is 6g / 10min.

[0036] The polycarbonate particles are Bayer ET3113.

[0037] The silicone flame retardant is hydroxyphenylsiloxane.

[0038] The anti-dripping agent is silicone coated polytetrafluoroethylene.

[0039] The antioxidant used is hindered phenol antioxidant: phosphite antioxidant in a ratio of 1:1.

[0040] The anti-hydrolysis agent is of carbodiimide type.

[0041] The heat stabilizer is a calcium zinc composite stabilizer.

[0042] The dispersant is dimethyl silicone oil.

[0043] The toner content in the black masterbatch is 32%.

[0044] The preparation method of flame retardant polycarbonate material (anti-humidity, heat, aging and environmentally friendly) is as follows:

[0045] The polycarbonate granules and the polycarbonate powder are dried at 120° C. for 4 hours, and the organosilicon flame retardant, the anti-dripping agent, the anti-hydrolysis agent, the heat stabilizer, the antioxidant and the anti-dripping agent are dried at 80° C. for 4 hours.

[0046] The dried organic silicon flame retardant and anti-dripping agent are mixed in a high-speed mixer and then prepared into various single-function masterbatches using a twin-screw extruder.

[0047] The prepared single-function masterbatch, polycarbonate raw material, black masterbatch, release agent and antioxidant are mixed by a high-speed mixer, and then the final product is prepared by a twin-screw extruder.

[0048] The twin-screw length-diameter ratio is 40:1.

[0049] A too high aspect ratio of the twin screw will cause the flame retardant reaction time to be too long, the flame retardant effect to be attenuated, and the mechanical properties to decrease. During actual production, it should be adjusted as needed.

[0050] Regardless of whether the above components are prepared through single-functional masterbatch or directly added, the final mass components remain consistent with those mentioned in this embodiment.

[0051] Example 2

[0052] The difference from Example 1 is that the amount of anti-hydrolysis agent is increased to 1 part, and the weight of the changed part is deducted from the polycarbonate pellets. The rest is consistent with Example 1.

[0053] Example 3

[0054] The difference from Example 1 is that the heat stabilizer is increased to 1 part, and the weight of the changed part is deducted from the polycarbonate pellets. The rest is consistent with Example 1.

[0055] Example 4

[0056] The difference from Example 1 is that the amount of the organosilicon flame retardant is reduced to 1.2 parts, and the weight of the changed part is deducted from the polycarbonate pellets. The rest is the same as Example 1.

[0057] Example 5

[0058] In this embodiment, the mass fraction of each component in the flame retardant polycarbonate material is as follows:

[0059] 89.4 parts of polycarbonate granules, 3 parts of polycarbonate powder, 0.4 parts of sulfonate flame retardant, 0.8 parts of silicone flame retardant, 0.4 parts of anti-dripping agent, 0.1 parts of antioxidant, 0.2 parts of release agent, 0.1 parts of dispersant, 2.5 parts of black masterbatch. Among them,

[0060] The average molecular weight of the polycarbonate is 50,000.

[0061] Under the test conditions of 1.2kg, it is 6g / 10min.

[0062] The polycarbonate particles are Bayer ET3113.

[0063] The silicone flame retardant is hydroxyphenylsiloxane.

[0064] The anti-drip agent is silicone coated polytetrafluoroethylene.

[0065] The antioxidant is a hindered phenol antioxidant and a phosphite antioxidant in a ratio of 1:1.

[0066] The anti-hydrolysis agent is of carbodiimide type.

[0067] The heat stabilizer is a calcium-zinc composite stabilizer.

[0068] The dispersant is dimethyl silicone oil.

[0069] The toner content in the black masterbatch is 32%.

[0070] The preparation method of flame retardant polycarbonate material (thin-wall molding temperature resistant) is as follows:

[0071] The polycarbonate granules and the polycarbonate powder were dried at 120° C. for 4 hours, and the organosilicon flame retardant, toughening agent, release agent, antioxidant and anti-dripping agent were dried at 80° C. for 4 hours.

[0072] The dried polycarbonate granules, polycarbonate powder, organosilicon flame retardant and anti-dripping agent are mixed in a high-speed mixer, and then the mixed materials are extruded through a twin-screw extruder to prepare multifunctional flame retardant masterbatch.

[0073] The dried polycarbonate granules, polycarbonate powder, dispersant and anti-dripping agent are mixed in a high-speed mixer, and the mixed materials are extruded through a twin-screw extruder to prepare anti-dripping masterbatch.

[0074] The twin-screw length-diameter ratio is 40:1.

[0075] A too high aspect ratio of the twin screw will cause the flame retardant reaction time to be too long, the flame retardant effect to be attenuated, and the mechanical properties to decrease. During actual production, it should be adjusted as needed.

[0076] The above-mentioned polycarbonate pellets, multifunctional flame retardant masterbatch, anti-drip masterbatch, anti-hydrolysis agent, thermal stabilizer, dispersant, antioxidant and black masterbatch are mixed in a high-speed mixer and then extruded by a twin-screw extruder to obtain the final product, the final mass fraction of which should be consistent with the components mentioned in this embodiment.

[0077] Example 6

[0078] The difference from Example 5 is that the number of black master batches is increased to 3.

[0079] Example 7

[0080] The difference from Example 5 is that the amount of antioxidant is increased to 0.2 parts, and the rest remains the same as Example 5.

[0081] Example 8

[0082] The difference from Example 5 is that the added proportion of the anti-dripping agent is increased by 0.5 parts, and the rest is the same as Example 5.

[0083] Comparative Example 1

[0084] The components are the same as those in Example 1, but all raw material components are added into a high-speed mixer at once and then extruded at one time (ie, flame retardant masterbatch is not prepared).

[0085] Comparative Example 2

[0086] The difference from Example 1 is that no anti-hydrolysis agent is added.

[0087] Comparative Example 3

[0088] The difference from Example 1 is that no heat stabilizer is added.

[0089] Comparative Example 4

[0090] The difference from Example 1 is that no organosilicon flame retardant is added.

[0091] Comparative Example 5

[0092] The difference from Example 1 is that no anti-dripping agent is added.

[0093] Comparative Example 6

[0094] The difference from Example 5 is that the anti-dripping agent is increased to 1.2 parts, and the rest is the same as Example 5.

[0095] Comparative Example 7

[0096] Compared with Example 5, the amount of black masterbatch added is reduced to 1 part, and the rest remains the same as Example 5.

[0097] All the above examples and comparative examples were prepared by cast extrusion to obtain films with a thickness of 0.25 mm. The films were tested according to the corresponding test standards to obtain the following Table 1:

[0098]

[0099]

[0100] As shown in Table 1, the 0.5 mm film samples prepared from the halogen-free flame-retardant polycarbonate modified material with excellent thin-wall molding and temperature resistance provided in Examples 1-8 have no problems with film processing and molding feasibility, and the prepared film products have no light transmittance problems. The UL-94 flame retardant test can reach V0 level flame retardancy. The film products can still maintain flame retardancy VO after undergoing 1500 hours of double 85 aging test without cracking or deformation problems.

[0101] Compared with Example 1, when comparative example 1 is prepared into the corresponding functional masterbatch, its flame retardant performance cannot reach the flame retardant V0 level, mainly because the dispersion and reaction of the flame retardant lead to the attenuation and degradation of the flame retardant component.

[0102] Comparison between Comparative Example 2 and Example 1 shows that without adding an anti-hydrolysis agent, the flame retardant performance of the material will decline after double 85 aging.

[0103] Comparison between Comparative Example 3 and Example 1 shows that without adding a heat stabilizer, the material's deformation resistance declines after double 85 aging.

[0104] Comparing Comparative Example 4 with Example 1, without adding the organosilicon flame retardant, the flame retardant performance of the material before and after aging obviously does not reach the UL-94 flame retardant V0 grade.

[0105] Comparing Comparative Example 5 with Example 1, without adding the organosilicon flame retardant, the flame retardant performance of the material before and after aging obviously does not reach the UL-94 flame retardant V0 grade.

[0106] Compared with Example 5, in Comparative Example 6, when the overall content of the anti-dripping agent is too high, the material cannot be formed during the film forming process.

[0107] Comparison of Comparative Example 7 with Example 5 shows that when the amount of black masterbatch added is too low, the film product will have light transmittance problems.

[0108] The above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit the same. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical concepts disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A flame retardant polycarbonate material, characterized in that: The following components are included in the following mass fractions: The polycarbonate raw material is 80-99 parts, the dispersant is 0.05-2 parts, the silicone flame retardant is 0.1-10 parts, the anti-dripping agent is 0.1-0.8 parts, the anti-hydrolysis agent is 0.3-2 parts, the heat stabilizer is 0.1-1 parts, the antioxidant is 0.05-1 parts, and the black masterbatch is 1-4 parts.

2. The flame retardant polycarbonate material according to claim 1, characterized in that: The polycarbonate raw material is composed of one or both of polycarbonate granules and polycarbonate powder; The average molecular weight of the polycarbonate is 50000Da-70000Da; The melt mass flow rate is not higher than 6.5g / 10min under the test conditions of 300℃ and 1.2kg; The particle size of the polycarbonate raw material is 10um-500um.

3. The flame retardant polycarbonate material according to claim 1, characterized in that: The dispersant is composed of one or both of hydroxy silicone oil and dimethyl silicone oil; The viscosity of the dispersant at 25° C. ranges from 500 to 1000 cST.

4. The flame retardant polycarbonate material according to claim 1, characterized in that: The organic silicon flame retardant is composed of one or more of hydroxyphenylsiloxane, organic silsesquioxane, and methylphenylsilsesquioxane.

5. The flame retardant polycarbonate material according to claim 1, characterized in that: The anti-dripping agent is composed of one or more of powdered polytetrafluoroethylene, polytetrafluoroethylene wax, and silicone-coated polytetrafluoroethylene; The content of polytetrafluoroethylene in the silicone-coated polytetrafluoroethylene is ≥80%.

6. The flame retardant polycarbonate material according to claim 1, characterized in that: The anti-hydrolysis agent is composed of one or more of carbodiimide type, isocyanate type and polyester type.

7. The flame retardant polycarbonate material according to claim 1, characterized in that: The heat stabilizer is composed of one or more of calcium-zinc composite stabilizer, organic tin stabilizer, and rare earth stabilizer.

8. The flame retardant polycarbonate material according to claim 1, characterized in that: The toner content in the black masterbatch is 25%-40%.

9. The flame retardant polycarbonate material according to claim 1, characterized in that: The antioxidant is composed of one or more of hindered phenol antioxidants and phosphite antioxidants.

10. A method for preparing a flame retardant polycarbonate material, characterized in that: The preparation method of the flame retardant polycarbonate material according to any one of claims 1 to 9 comprises the following steps: The components are taken according to the ratio and formed by a twin-screw one-step process or a twin-screw multi-step process.

11. The method for preparing a flame retardant polycarbonate material according to claim 10, characterized in that: During the processing, the temperature is controlled at 220-270℃.

12. The method for preparing a flame retardant polycarbonate material according to claim 10, characterized in that: When twin-screw processing is adopted, the aspect ratio of the twin-screw is 36:1, 40:1; 44:1, 48:

1.

13. The flame retardant polycarbonate material according to claims 1-9 is used in a film formed by casting or calendering extrusion.

14. The film according to claim 13 is used in the 3C electronic products industry, the new energy battery industry, and the energy storage industry.

Citation Information

Patent Citations

  • High-impact-resistance thin-wall flame-retardant polycarbonate material and preparation method thereof

    CN119144139A